Assessment of adiposity in psoriatic patients by dual energy X-ray absorptiometry compared to conventional methods - Michelle dos Santos Diniz; Nádia Couto Bavoso; Adriana Maria Kakehasi; Márcio Weissheimer Lauria; Maria Marta Sarquis Soares; Jackson Machado-Pinto (Sociedade Brasileira de Dermatologia, 2016)
Abstract BACKGROUND: Obesity is considered a chronic low-grade inflammatory disease that shares mediators of inflammation with psoriasis, such as TNF-α and IL-6. The relationship between these two conditions involves factors such as predisposition and response to therapy, in addition to an association with cardiovascular disease. OBJECTIVES: The aim of the present study was to investigate the prevalence of adiposity as determined by body mass index (BMI), waist circumference (WC), and dual energy X-ray absorptiometry (DXA) evaluation in patients with psoriasis. METHODS: BMI, WC and body composition by DXA were measured in 42 psoriatic patients without joint complaints and in 41 control patients using standard procedures. In the comparison between cases and controls, we used Pearson's Χ2 test or Fisher's exact test, and the nonparametric Mann-Whitney test. The difference between the diverse classification methods for obesity was evaluated using McNemar's test. To test the level of agreement between those variables, we used the weighted kappa coefficient. RESULTS: There was no difference in the prevalence of obesity among cases and controls. Both BMI and WC had low agreement with measures of body fat evaluated by DXA. With the use of DXA scanning, prevalence of overweight and obesity in patients with psoriasis was 83.3%, which constitutes a strong evidence of the need for intervention on this metabolic parameter. CONCLUSION: Dual energy X-ray absorptiometry was more capable of identifying obesity compared with BMI and WC both in psoriatic and control patients.